2006
DOI: 10.1093/pasj/58.2.423
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Simulation of Solar Emerging Flux Using the Earth Simulator I. Magnetic Rayleigh-Taylor Instability at the Top of the Emerging Flux as the Origin of Filamentary Structure

Abstract: We present the results of three-dimensional magnetohydrodynamic simulations of solar emerging flux and its interaction with preexisting coronal field. In order to resolve the fine structures and the current sheets, we used high-resolution grids with up to $800 \times 400 \times 620$ points; the calculation was carried out using the Earth Simulator. The model set up is an extension of a previous two-dimensional simulation by Yokoyama and Shibata (1995) to include the variation along the third direction. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 77 publications
4
38
0
Order By: Relevance
“…This non-linear phase agrees qualitatively with the observations of turbulent plumes and bubbles in prominences (Isobe et al 2005;Berger et al 2008Berger et al , 2010Berger et al , 2011Heinzel et al 2008;Ryutova et al 2010) and has even been used to infer plasma properties from observational features (Hillier et al 2012b). The presence of the RTI has also been confirmed numerically in more general prominence models with 3D geometry (Isobe et al 2006;Hillier et al 2011Hillier et al , 2012a.…”
Section: Introductionsupporting
confidence: 81%
“…This non-linear phase agrees qualitatively with the observations of turbulent plumes and bubbles in prominences (Isobe et al 2005;Berger et al 2008Berger et al , 2010Berger et al , 2011Heinzel et al 2008;Ryutova et al 2010) and has even been used to infer plasma properties from observational features (Hillier et al 2012b). The presence of the RTI has also been confirmed numerically in more general prominence models with 3D geometry (Isobe et al 2006;Hillier et al 2011Hillier et al , 2012a.…”
Section: Introductionsupporting
confidence: 81%
“…This is consistent with the RT-CD theory because larger toroidal magnetic field gives smaller U 2 and hence the RT effect is weaker. As the flux tube emerges from the convection zone to the solar corona, a filamentary structure can form at the top of the emerging flux tube as a result of MRT instability 43,44 under solar gravity. The filamentary structure is found to be parallel to the surface magnetic field, consistent with the interchange mode of MRT instability.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In fact, the emergence of the axis proceeds more efficiently when a curved (convex-up) flux tube is initially assumed MacTaggart and Hood, 2009). Archontis et al (2004Archontis et al ( , 2005Archontis et al ( , 2007, Isobe et al (2005Isobe et al ( , 2006, and Galsgaard et al (2005Galsgaard et al ( , 2007 have studied the interaction of emerging and preexisting fields in various three-dimensional configurations (see Section 4.3). A series of works done by Manchester (Manchester IV, 2001;Manchester IV et al, 2004;Manchester IV, 2007) have shown the origin of shear flows observed on the surface (see Section 4.3).…”
Section: Latest Progressmentioning
confidence: 99%